The Evolving Landscape of Neurotoxicity by Unconjugated Bilirubin: Role of Glial Cells and Inflammation - Brites, Dora (Frontiers in Pharmacology, 2012)
Unconjugated hyperbilirubinemia is a common condition in the first week of postnatal life. Although generally harmless, some neonates may develop very high levels of unconjugated bilirubin (UCB), which may surpass the protective mechanisms of the brain at preventing UCB accumulation. In this case, both short-term and long-term neurodevelopmental disabilities, such as acute and chronic UCB encephalopathy, known as kernicterus, or more subtle alterations designed as bilirubin-induced neurological dysfunction (BIND) may be produced. There is a tremendous variability in babies’ vulnerability towards UCB for reasons not yet explained, but preterm birth, sepsis, hypoxia and haemolytic disease are comprised as risk factors. Therefore, UCB levels and neurological abnormalities are not strictly correlated. Even nowadays, the mechanisms of UCB neurotoxicity are still unclear, as are specific biomarkers, and little is known about lasting sequelae attributable to hyperbilirubinemia. On autopsy, UCB was shown to be within neurons, neuronal processes and microglia, and to produce loss of neurons, demyelination and gliosis. In isolated cell cultures, UCB was shown to impair neuronal arborization and to induce the release of proinflammatory cytokines from microglia and astrocytes. However, cell dependent-sensitivity to UCB toxicity and the role of each nerve cell type remain understood. This review provides a comprehensive insight into cell susceptibilities and molecular targets of UCB in neurons, astrocytes, and oligodendrocytes, and on phenotypic and functional responses of microglia to UCB. Interplay among glia elements and cross-talk with neurons, with a special emphasis in the UCB-induced immunostimulation, and the role of sepsis in BIND pathogenesis are highlighted. New and interesting data on the anti-inflammatory and antioxidant activities of different pharmacological agents are also presented, as novel and promising additional therapeutic approaches to BIND.